Colloidal quantum dots and two‐dimensional material heterostructures for photodetector applications - Jingying Luo; Gurpreet Singh Selopal; Xin Tong; Zhiming Wang (Electron)
Abstract Photodetectors (PDs) are optoelectronic devices that convert optical signals into electrical responses. Recently, there has been a tremendous increase in research interest in PDs based on colloidal quantum dots (QDs) and two‐dimensional (2D) material heterostructures owing to the strong light‐absorption capacity and the well‐adjustable band gap of QDs and the superior charge carriers transfer ability of 2D materials. In particular, the heterojunction formed between QDs and 2D materials can effectively enhance the separation and transport of photogenerated charge carriers, which is expected to establish PDs with ultrahigh photoconductive gain, high responsivity, and detectivity. This review aimed to summarize the state‐of‐the‐art advances in the research of QDs/2D material nanohybrid PDs, including the device parameters, architectures, working mechanisms, and fabrication technologies. The progress of hybrid PDs based on the heterojunction of QDs with different 2D materials, along with their innovative applications, are comprehensively described. In the end, the challenges and feasible strategies in future research and development are briefly proposed.